Clinical Abnormalities in the Hemogram of HIV-infected Children - Daminov Turgunpolat., Tuychiyev Laziz., Khudaykulova Gulnara., Rakhmatullayeva Shakhnoza (International Journal of Advanced Science and Technology, 2020)
In Uzbekistan, the number of HIV-infected children born from HIV-infected mothers decreased almost fivefold between 2009 and 2013. In the period from September 2015 to January 2017, 124 patients aged 0 to 18 years with a diagnosis of HIV infection at various stages of its development were examined. During the examination, platelet aggregation activity, activated partial (partial) thromboplastin time, prothrombin index, thrombin time, and plasma fibrinogen concentration were determined. To assess the activity of the anticoagulation system, the orthophenanthroline test was used. We observed the formation of a deficiency of blood platelets in 14% of children with the second clinical stage of HIV infection and in 27% of children with the third stage of the disease. Currently, direct suppression of megakaryocytopoiesis in the hematopoietic tissue of the bone marrow under the influence of antiretroviral therapy and autoimmune destruction of megakaryocyte precursors are considered to be the alleged causes of platelet loss in the described situations.